FInancial Distress dan Variabel Yang Mempengaruhinya - Rita Kusumawati; Reisady Birnanitta (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to analyze the effect of liquidity, leverage, operating capacity and firm size on financial distress. The object of research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2012-2017. This study used purposive sampling method with 516 samples. Using logistic regression, this research resulted leverage has a positive effect on financial distress, operating capacity has a negative effect on financial distress. while company size and liquidity have no influence on financial distress